2020
DOI: 10.3389/fevo.2020.569620
|View full text |Cite|
|
Sign up to set email alerts
|

The Spatial Signature of Introgression After a Biological Invasion With Hybridization

Abstract: The accumulation of genome-wide molecular data has emphasized the important role of hybridization in the evolution of many organisms, which may carry introgressed genomic segments resulting from past admixture events with other taxa. Despite a number of examples of hybridization occurring during biological invasions, the resulting spatial patterns of genomic introgression remain poorly understood. Preliminary simulation studies have suggested a heterogeneous spatial level of introgression for invasive taxa aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 88 publications
2
32
2
Order By: Relevance
“…The decrease of introgressed genes in the wild boars' genomes with the increase in the distance from the invasion source ( figure 4 ) and with time is likely to be caused from the wild boar being most abundant in the evacuated zone [ 10 ] and the random mating tendencies of wild boar in this area (electronic supplementary material, figure S6), which in turn, increases the opportunity of backcross generations with wild boar and less chance of direct contact between remaining invasive pigs or other hybrids. Particularly, our result may be an indication of demic diffusion [ 25 ] in the wild, in which the invader gene pool is progressively diluted along the expansion due to recurrent admixture with the native species. This contrasts with reported hybridization in European wild boar populations where, despite new developments of intensive indoor pig farming, older hybridization events are being followed-up by interbreeding among hybrids, or recent escaped pigs, resulting in ongoing introgression on multiple occasions [ 42 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The decrease of introgressed genes in the wild boars' genomes with the increase in the distance from the invasion source ( figure 4 ) and with time is likely to be caused from the wild boar being most abundant in the evacuated zone [ 10 ] and the random mating tendencies of wild boar in this area (electronic supplementary material, figure S6), which in turn, increases the opportunity of backcross generations with wild boar and less chance of direct contact between remaining invasive pigs or other hybrids. Particularly, our result may be an indication of demic diffusion [ 25 ] in the wild, in which the invader gene pool is progressively diluted along the expansion due to recurrent admixture with the native species. This contrasts with reported hybridization in European wild boar populations where, despite new developments of intensive indoor pig farming, older hybridization events are being followed-up by interbreeding among hybrids, or recent escaped pigs, resulting in ongoing introgression on multiple occasions [ 42 ].…”
Section: Discussionmentioning
confidence: 91%
“…Here, we evaluate the hypotheses that range expansion acts as resistance against hybridization, and that invasion success is dependent on the invaders' response to naturalization; both hypotheses have been often embedded in evolution [ 22 , 24 , 25 ]. Specifically, we determined the extent of the genetic introgression from invasive pigs into wild boar in Fukushima Prefecture after the FDNPP accident, and observed the longevity of introgressed alleles or organelles to evaluate the above hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…Despite spatially explicit computer simulations are computationally slow compared with other simulation approaches (i.e., the standard coalescent), these simulations are highly realistic by explicitly taking into account evolutionary, geographic, and environmental information ( Dunning et al 1995 ; Epperson et al 2010 ; Benguigui and Arenas 2014 ). We performed spatially explicit computer simulations of genetic data with the framework SPLATCHE3 ( Currat et al 2019 ), a simulator that has been widely used for human evolutionary studies (e.g., Currat and Excoffier 2004 , 2005 ; Ray 2005 ; Francois et al 2010 ; Alves et al 2016; Pimenta et al 2017 ; Branco and Arenas 2018 ; Quilodrán et al 2020 ). Basically, this framework consists of the following three main steps: 1) A forward-in-time simulation (from the past to the present) of the entire population upon a user-specified landscape, demographic and migration model.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic markers have been used to identify the genetic makeup of invasive populations, and understand how genome level processes contribute to invasion of diverse natural ecosystems (Bock et al, 2015;Colautti and Lau, 2015;Dlugosch et al, 2015;Rius et al, 2015b;Mounger et al, 2021a). Studies in the native and introduced ranges have reported that many invasive populations undergo only modest reductions in genetic variation due to multiple introductions (Stepien et al, 2005;Dlugosch and Parker, 2008a;Snyder and Stepien, 2017;Flucher et al, 2021), hybridization (Fitzpatrick et al, 2009;Scascitelli et al, 2010;van Riemsdijk et al, 2018van Riemsdijk et al, , 2020Quilodrán et al, 2020), or Allee effects that result from reverse density dependence or cooperation (Kramer and Sarnelle, 2008;Aikio et al, 2010;Rius et al, 2015b). For example, sequences of mitochondrial DNA revealed multiple invasion sources for both dreissenid mussels and goby species of fish, and that this diversity was correlated to rapid spread and colonization success in a variety of habitats (Stepien et al, 2005).…”
Section: Discoveries and Limitations Of Genomic Studies Of Diverse Invasive Speciesmentioning
confidence: 99%